Family of strangers - Richards, Emilie 1948- (Waterville, Maine Wheeler Publishing, a part of Gale, a Cengage Company, 2019)
"Could a lifetime of memories...be a lifetime of lies? All her life, Ryan Gracey watched her perfect older sister from afar. Knowing she could never top Wendy's achievements, she didn't even try. Instead Ryan forged her own path while her family barely seemed to notice. Now Wendy shares two little girls with her perfect husband, while Ryan mourns the man she lost after a nearly fatal mistake in judgment. The sisters' choices have taken them in different directions, which is why Ryan is stunned when Wendy calls, begging for her help. There's been a murder--and Wendy believes she'll be wrongfully accused. While Wendy lies low, Ryan moves back to their hometown to care for the nieces she hardly knows. The sleuthing skills she's refined as a true-crime podcaster quickly rise to the surface as she digs for answers with the help of an unexpected ally. Yet the trail of clues Wendy's left behind leads to nothing but questions. Blood may be thicker than water, but what does Ryan owe a sister who becomes more and more a stranger with every revelation? Is Wendy, who always seemed so perfect, just a perfect liar--or worse?"--
107682
Keywords: Sisters -- Fiction; Sibling rivalry; Malicious accusation; Murder -- Investigation; Podcasters; Marriage; Families; Man-woman relationships; Large type books; Detective and mystery fiction; Thrillers (Fiction)